1982
DOI: 10.1161/01.hyp.4.5_pt_2.iii99
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes in DOCA hypertension. Influence of a low protein diet.

Abstract: SUMMARY The goal of this study was to characterize the influence of a low protein d iet on vascular changes induced by deoxycorticosterone acetate (DOCA) hypertension. DOCA hypertensive and control normotensive rats were placed on a low protein (5%) diet for 4 weeks. This intervention blocked the further increase in systolic blood pressure of rats treated with DOCA; systolic blood pressures of control rats were not influenced by the low protein diet. The sensitivity of isolated mesenteric arteries to norepinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This lack of change may be due to the fact that no change in the sensitivity to NE itself was observed. Moreland et al, 6 however, have observed an increase in NE responsiveness of VSM from DOCA-salt hypertensive rats, which they suggest is mediated by an increase in the membrane stores of Ca 2+ . Although the exact mechanism (or mechanisms) by which the Ca 2+ sensitivity is increased in VSM from DOCA-salt hypertensive rats cannot be determined from this study, two possible general mechanisms are suggested.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This lack of change may be due to the fact that no change in the sensitivity to NE itself was observed. Moreland et al, 6 however, have observed an increase in NE responsiveness of VSM from DOCA-salt hypertensive rats, which they suggest is mediated by an increase in the membrane stores of Ca 2+ . Although the exact mechanism (or mechanisms) by which the Ca 2+ sensitivity is increased in VSM from DOCA-salt hypertensive rats cannot be determined from this study, two possible general mechanisms are suggested.…”
Section: Resultsmentioning
confidence: 90%
“…Calmodulin levels are not altered in VSM from DOCA-salt hypertensive rats, 15 and the actomyosin content and actin-to-myosin ratio remain unchanged. 6 To our knowledge, studies on other components involved in the contractile process of VSM from hypertensive animals, such as myosin light chain kinase, have not been performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This response of the adrenergic nerve ending may partially explain the increased sensitivity found in this study to norepinephrine of the vascular smooth muscle in hypertension. It is proposed that the smooth muscle increases its sensitivity to the catecholamine in response to the reduced release of the transmitter from 28 that accompanies the development of hypertension results in an effective denervation of the smooth muscle cells that become increasingly farther away from their adrenergic supply at the adventitial-medial border of the blood vessel. This latter speculation is supported by the observation that the vascular cells nearest the luminal surface are more sensitive to norepinephrine whereas those nearest the external surface are less sensitive to the catecholamine.…”
Section: Release and Pharmacological Displacement Of Norepinephrine Fmentioning
confidence: 99%